2019
DOI: 10.1111/bph.14854
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilation induced by PGE2 is impaired in Group III pulmonary hypertension

Abstract: Background and purpose: In patients with pulmonary hypertension (PH) associated with lung disease and/or hypoxia (Group III), a reduction of pulmonary vascular tone and tissue hypoxia are considered therapeutically beneficial. Prostaglandin (PG) E2 and PGI2 induce potent relaxation of human bronchi from non-PH (control) patients via EP4 and IP receptors, respectively. However, the effects of PGE2/PGI2 and their mimetics on human bronchi from PH-patients are unknown. Our aim was to compare the relaxant effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…EP4-receptor expression was not modified in pulmonary arteries or lungs derived from chronically hypoxic PH rats or monocrotaline-treated rats and patients with PAH; this was demonstrated by real-time PCR, Western blot, and immunohistochemical studies (Lai et al, 2008;Li et al, 2018;Fan et al, 2019a). However, our recent study demonstrated that there is a decrease of EP4-receptor expression in bronchi derived from PH group-III patients by Western blot and real-time PCR techniques (Ozen et al, 2020b). Another recent study performed on hypoxia-induced PH rats revealed that the beneficial effect of beraprost (PGI 2 analog) is mediated via the EP4 receptor-related pathway (Tian et al, 2019).…”
Section: Ep1-4 and Ip Receptors In Human And Rodentsmentioning
confidence: 71%
See 4 more Smart Citations
“…EP4-receptor expression was not modified in pulmonary arteries or lungs derived from chronically hypoxic PH rats or monocrotaline-treated rats and patients with PAH; this was demonstrated by real-time PCR, Western blot, and immunohistochemical studies (Lai et al, 2008;Li et al, 2018;Fan et al, 2019a). However, our recent study demonstrated that there is a decrease of EP4-receptor expression in bronchi derived from PH group-III patients by Western blot and real-time PCR techniques (Ozen et al, 2020b). Another recent study performed on hypoxia-induced PH rats revealed that the beneficial effect of beraprost (PGI 2 analog) is mediated via the EP4 receptor-related pathway (Tian et al, 2019).…”
Section: Ep1-4 and Ip Receptors In Human And Rodentsmentioning
confidence: 71%
“…In a similar way, in a rat model of PH, iloprost treatment was effective at reducing bronchial hyper-reactivity induced by methacholine (Habre et al, 2011). Although the majority of effects of PGI 2 analogs on bronchial muscle tone have been attributed to the IP receptor, EP4 and DP1 receptors may also contribute to the actions of treprostinil, particularly at higher analog concentrations (Ozen et al, 2020b).…”
Section: A Bronchial Smooth Muscle Cellsmentioning
confidence: 79%
See 3 more Smart Citations